Deepening apartheid: The political geography of colonizing Israel/Palestine - Yiftachel, Oren (Frontiers in Political Science, 2023)
The paper analyzes the regime in Israel/Palestine using a political geographical perspective. It demonstrates how a combination of colonial, national, capitalist and liberal forces have put in train a process of “deepening apartheid” in the entire territory controlled by Israel—between River and Sea. This undeclared regime has been established to guard the 'achievements' of settler colonial Judaization of the land and the domination of the Jewish minority. As described by the Rome Statute, it has become an institutionalized regime of systematic oppression and domination by one group over others, with the intention of maintaining that regime. Hence the political geographical analysis shows clearly that the wide description in academic and international circles of Israel as “Jewish and democratic,” is based on a denial of the clear racialized hierarchy of civil statuses. This setting enhances Jewish supremacy (using different methods) it in all regions, while Palestinians are fragmented into lower rungs on the ethnic hierarchy—de facto and de jure—thereby contradicting the tenets of democratic civil equality. Theoretically, the paper draws on the links between settler colonial expansion, the rise of ethnocracy, partial liberalization under global capitalism, and the making of apartheid. It shows that historically Jewish colonization of Palestine—the underlying logic of the regime—has advanced in six main historical-geographical stages, encountering persistent, and at times violent, Palestinian resistance. The paper then analyzes in more detail the emergence of one regime between River and Sea, in which the state uses military, spatial, economic, and legal powers, as well as geopolitical maneuvering (particularly US support) to oppress Palestinians, while promoting democratic rights and economic development among Jews. This has enabled Israel to integrate and “whiten” Mizrahi and other Jewish groups into mainstream Zionism. Rivaling Palestinian political projects have been fragmented, ghettoized, attacked violently, and severely weakened. The paper shows how Jewish colonization, on both sides of the Green Line (which has also included some tactical withdrawals), has led to the establishment of four hierarchical types of citizenship, governed as “separate and unequal”. The relations between the groups resemble the racialized categories used in Apartheid South Africa and include (a) “White”—Jewish Israelis—with full citizenship rights; (b) “Colored”—Palestinian Arabs with Israeli citizenship with partial rights; (c) “Black”—Palestinians under occupation lacking citizenship or political rights; (d) “Gray”—an emerging group, consisting of non-citizen migrants and asylum seekers.